De novo DQ donor‐specific antibodies are associated with worse outcomes compared to non‐DQ de novo donor‐specific antibodies following heart transplantation. Issue 4 (5th March 2017) - Cole, Robert Townsend; Gandhi, Jonathan; Bray, Robert A.; Gebel, Howard M.; Morris, Alanna; McCue, Andrew; Yin, Michael; Laskar, S. Raja; Book, Wendy; Jokhadar, Maan; Smith, Andrew; Nguyen, Duc; et al.
Abstract: Background: Antibody‐mediated rejection (AMR) resulting from de novo donor‐specific antibodies (dnDSA) leads to adverse outcomes following heart transplantation (HTx). It remains unclear what role dnDSA to specific HLA antigens play in adverse outcomes. This study compares outcomes in patients developing dnDSA to DQ antigens with those developing non‐DQ dnDSA and those free from dnDSA. Methods: The present study was a single‐center, retrospective analysis of 122 consecutive HTx recipients. The primary outcome was a composite of death or graft dysfunction. Results: After 3.3 years of follow‐up, 31 (28%) patients developed dnDSA. Mean time to dnDSA was 539 days. Of 31 patients, 19 developed DQ antibodies and 12 developed non‐DQ antibodies. Compared to non‐DQ dnDSA, DQ antibodies presented with higher MFI values ( P =.001) were more likely persistent ( P =.001) and appeared later post‐HTx (654 vs 359 days, P =.035). In a multivariable analysis, DQ dnDSA was associated with increased risk of the primary endpoint (HR 6.15, 95% CI 2.57‐14.75, P =.001), whereas no increased risk was seen with non‐DQ dnDSA ( P =.749). Conclusions: dnDSA to DQ antigens following HTx are associated with increased risk of death and graft dysfunction.